Empowering Talian Kereng Village farmer groups through independent organic fertilizer production based on local resources for sustainable agriculture - Rosalina, Reny; Hermayantiningsih, Dwi; Priyadi, Muhammad; Decenly, Decenly; Putri, Alayya Adistia; Sametri, Ni Wayan Septia (Universitas Muhammadiyah Magelang, 2025)
Talian Kereng Village, located in Katingan Hilir District, Central Kalimantan, faces challenges regarding the availability of fertilizers for upland rice farmers on peatlands, with a heavy reliance on government-subsidized chemical fertilizers. To address this issue, a community empowerment program was implemented to promote independent organic fertilizer production using local resources. The program involved education and training for the Maju Bersama farmer group on the production of decomposers, liquid organic fertilizer (eco enzyme), and compost from household waste and harvest residues. The results showed a significant increase in knowledge, where initially, 53.9% of participants had limited understanding of decomposer and eco enzyme production, but after the training, 95.3% of participants fully comprehended the material. Furthermore, all participants became skilled in producing organic fertilizers. This program is expected to enhance farmers' self-sufficiency in meeting fertilizer needs, reduce dependence on chemical fertilizers, and support agricultural sustainability in Talian Kereng Village.